2019
DOI: 10.14260/jemds/2019/280
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Epidemiological Study of Warts in a Tertiary Care Hospital

Abstract: BACKGROUND Warts, which are also called as Verrucae are the commonest viral infections encountered in the dermatology practice. Warts are caused by Human Papilloma Virus (HPV). We wanted to study the clinical and epidemiological aspects of warts and determine the distribution of warts in relation to age, sex, occupation and socioeconomic status. METHODS The present study was conducted in a sample of 200 clinically diagnosed cases of Warts attending the outpatient Department of DVL. A clinico-epidemiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…6 Previous population studies showed that the distribution of common warts was 2-20% in school-age children, 10% in young adults, and 3.5% among adults, and the prevalence decreased with age. 1,8 This observation could be explained by the fact that where there are more chances of contact in schools, colleges, and workplaces, the transmission of HPV is enhanced. Adults are more prone to trauma secondary to more physical activities or participation in sports enhancing infection.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous population studies showed that the distribution of common warts was 2-20% in school-age children, 10% in young adults, and 3.5% among adults, and the prevalence decreased with age. 1,8 This observation could be explained by the fact that where there are more chances of contact in schools, colleges, and workplaces, the transmission of HPV is enhanced. Adults are more prone to trauma secondary to more physical activities or participation in sports enhancing infection.…”
Section: Discussionmentioning
confidence: 99%